IJNS 2020
DOI: 10.54216/ijns.010102
|View full text |Cite
|
Sign up to set email alerts
|

A New Score Function of Pentagonal Neutrosophic Number and its Application in Networking Problem

Abstract: The pentagonal neutrosophic number is an extended version of single typed neutrosophic number. Real-humankind problems have different sorts of ambiguity in nature and amongst them; one of the important problems is solving the networking problem. In this contribution, the conception of pentagonal neutrosophic numbers has been focused on a distinct framework of reference. Here, we develop a new score function and its estimation has been formulated from different perspectives. Further, a time computing-based netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The notion of neutrosophic logic is an extension of intuitionistic fuzzy logic by putting indeterminacy item (I) where I 2 = I, ..., I n = I, 0.I = 0; n ∈ N and I −1 is undened (see [23], [36]). Neutrosophic logic has plenty of applications in many areas of sciences including multicriteria decision making [33], [22], [29], machine learning [6], [31], intelligent disease diagnosis [34], [11], communication services [8], pattern recognition [32], social network analysis and e-learning systems [24], physics [38], sequences spaces [15] and many others. Neutrosophic logic has helped many multicretia decision-making problems eciently like nding credit rating, personal selection, among other.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of neutrosophic logic is an extension of intuitionistic fuzzy logic by putting indeterminacy item (I) where I 2 = I, ..., I n = I, 0.I = 0; n ∈ N and I −1 is undened (see [23], [36]). Neutrosophic logic has plenty of applications in many areas of sciences including multicriteria decision making [33], [22], [29], machine learning [6], [31], intelligent disease diagnosis [34], [11], communication services [8], pattern recognition [32], social network analysis and e-learning systems [24], physics [38], sequences spaces [15] and many others. Neutrosophic logic has helped many multicretia decision-making problems eciently like nding credit rating, personal selection, among other.…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2015, Helen (Helen and Uma 2015 ) established the idea of pentagonal fuzzy number, which has been extended by Christi (Christi and Kasthuri 2016 ) into pentagonal intuitionistic number to resolve the transportation problem. Recently, Chakraborty (Chakraborty et al 2019c , d , 2020 ; Chakraborty 2020 ) manifested a legerdemain conception of pentagonal fuzzy number and its various and distinct depiction in transportation field, graph theoretical problem, MCGDM and networking arena.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the truth membership function, indeterminacy membership function, and falsity membership functions are independent of each other [5] . The single-valued Neutrosophic sets are proposed by Wang et al [6] In 2014, Smarandache [7] introduced the refined n-valued Neutrosophic set, which is an extension of the Neutrosophic set and is more powerful for solving problems in very complex environments. In a refined n-valued Neutrosophic set, the occurrences are more than one with the possibility of the same or different truth membership function, indeterminacy membership function, and falsity membership functions.…”
mentioning
confidence: 99%
“…Chakraborty et al [8] came up with the Pentagonal Neutrosophic number (PNN) concept, and further suggested different techniques for deneutrosophication in Refs. [9,10].…”
mentioning
confidence: 99%